Literature Analysis on the Bornean Orangutan (Pongo Pygmaeus) Conservation Ecotourism in Tanjung Puting National Park, Waringin Barat City, Central Kalimantan - Puti Minang Anjarani; Marini Yunita; Grace Caroline Mailoa (International Journal of Travel, Hospitality and Events, 2022)
Purpose: The purpose of the study is to analyze the development of orangutans conservation ecotourism in Tanjung Puting National Park based on previous studies. Research Methods: The methodology used in this study is a literature review approach. Data collection was carried out by collecting data and information in the form of related journals from previous research. Results and Discussion: Synchronization and collaboration between stakeholders is important in improving the management of TPNP and implementing policies so that they are effective and optimal Implication: The dynamics of orangutan conservation are not being implemented according to their natural habitat. Keywords: ecotourism, conservation, Bornean orangutan (pongo pygmaeus).